Kontribusi Madrasah Aliyah dalam Meningkatkan Mutu Lulusan Berbasis Bimbingan Akademik (Studi Deskriptif Pada Mak Ponpes Al-Islam Kemuja) - Wahyudi, Wahyudi (Universitas Islam Negeri Raden Intan Lampung, 2019)
He took this problem based on the consideration that there were many educated unemployed workers, especially high schools and equals. This in turn will negatively affect the future of education which is not only a skilled and competitive generation of printing vehicles. This research specifically aims to determine the contribution of Islamic Religious Department of Al-Islam Islamic Boarding School in improving the quality of graduates, namely about readiness in optimizing all potential students to develop, thus providing an ideal guarantee for their future when entering the workforce. Data collection is mainly carried out through in-depth interviews (in-depth interviews), documentation (documentation) and reinforced by participant observation. Furthermore, the collected data is collided with relevant theories in order to obtain a complete picture of the objective conditions. The results of this study indicate that the contribution of Madrasah Aliyah Department of Religion Al-Islam Kemuja in improving the quality of graduates is by improving the quality of employment, understanding of students, improving academic achievement of students through religious majors and extracurricular programs and evaluating student learning outcomes